2012
DOI: 10.1155/2012/170958
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstriction Potency Induced by Aminoamide Local Anesthetics Correlates with Lipid Solubility

Abstract: Aminoamide local anesthetics induce vasoconstriction in vivo and in vitro. The goals of this in vitro study were to investigate the potency of local anesthetic-induced vasoconstriction and to identify the physicochemical property (octanol/buffer partition coefficient, pKa, molecular weight, or potency) of local anesthetics that determines their potency in inducing isolated rat aortic ring contraction. Cumulative concentration-response curves to local anesthetics (levobupivacaine, ropivacaine, lidocaine, and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
(69 reference statements)
1
22
0
Order By: Relevance
“…The n-octanol/buffer partition coefficients were 346 (bupivacaine), 115 (ropivacaine), 43 (lidocaine), and 21 (mepivacaine) [22]. Together with the findings of previous reports, our study shows that the magnitude of lipid emulsion-mediated reversal correlates with the lipid solubility of the local anesthetic [12,22]. One of underlying mechanisms of lipid emulsion-induced reversal of local anesthetic systemic toxicity is the "lipid sink" theory, which postulates that the lipid emulsion extracts local anesthetics from tissues into the lipid phase [23].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The n-octanol/buffer partition coefficients were 346 (bupivacaine), 115 (ropivacaine), 43 (lidocaine), and 21 (mepivacaine) [22]. Together with the findings of previous reports, our study shows that the magnitude of lipid emulsion-mediated reversal correlates with the lipid solubility of the local anesthetic [12,22]. One of underlying mechanisms of lipid emulsion-induced reversal of local anesthetic systemic toxicity is the "lipid sink" theory, which postulates that the lipid emulsion extracts local anesthetics from tissues into the lipid phase [23].…”
Section: Discussionsupporting
confidence: 78%
“…Intralipid®, which consists of 100% long-chain triglycerides, is commonly used to treat local anesthetic systemic toxicity, and Lipofundin® MCT/LCT, which consists of 50% long-chain triglycerides and 50% medium-chain triglycerides, is sometimes used to treat local anesthetic systemic toxicity [1-8]. Vaconstriction potency induced by local anesthetics is mainly determined by lipid solubility, among the physicochemical properties of local anesthetics [12]. However, studies investigating the ability of these two lipid emulsions (Lipofundin® MCT/LCT and Intralipid®) to extract local anesthetics and promote recovery from cardiac arrest induced by a toxic dose of bupivacaine have reported inconsistent results [16-19].…”
Section: Introductionmentioning
confidence: 99%
“…Local anesthetic (levobupivacaine, ropivacaine, and mepivacaine) treatment of isolated endothelium-denuded rat aorta produces vasoconstriction at low doses and vasodilation at high doses 7,17. Lipid emulsion also reverses high-dose local anesthetic-induced vasodilation in a manner dependent on the lipid solubility of local anesthetics 7.…”
Section: Methodsmentioning
confidence: 99%
“…Lipid emulsion also reverses high-dose local anesthetic-induced vasodilation in a manner dependent on the lipid solubility of local anesthetics 7. Thus, based on previous studies and lipid emulsion concentrations, which did not significantly affect high-dose local anesthetic-induced vasodilation in the preliminary experiment, both high-dose local anesthetic concentrations to produce vasodilation and lipid emulsion concentrations were chosen in our in vitro experiment 7,17. After administering high doses of local anesthetics [6×10 -4 M levobupivacaine (levobupivacaine group), 2×10 -3 M ropivacaine (ropivacaine group), and 7×10 -3 M mepivacaine (mepivacaine group)] to produce stable and sustained vasodilation in endothelium-denuded aorta precontracted with isotonic 60 mM KCl, high-dose local anesthetic-induced vasodilated aortas were treated with or without lipid emulsions (0.30, 0.49, 1.40, and 2.16%) for 5 min before the addition of norepinephrine.…”
Section: Methodsmentioning
confidence: 99%
“…[ 15 16 ] It was recently demonstrated that Levo is more lipophilic and is a more potent vasoconstrictor than Ropi. [ 23 ] We conjecture that these two properties can lead to greater delay in vascular absorption of 0.5% Levo versus its comparator.…”
Section: Discussionmentioning
confidence: 99%